ISSUES OF COMMERCIALIZATION OF PROJECTS FOR THE PRODUCTION OF INNOVATIVE PRODUCTS IN SMALL BUSINESSES - Babakhanov Jamolidin Yandirovich (Journal of Artificial Intelligence and Digital Economy, 2024)
The article develops proposals and recommendations on a theoretical basis for the commercialization of scientific projects, organizational mechanisms and the effective use of infrastructure to improve the efficiency of small businesses and production, especially in terms of product output. based on innovation